Efeito do desenho dos bancos na permanência dos usuários em espaços de uso público - Saquet, Taynan (2023)
Public space can be described as the place where public life happens and it is used for the common good, as well as being accessible and shared by a diversity of people. Along with these spaces there is street furniture, in the form of seats, trash cans, lightning, and others. Seats make the public space more habitable, contributing to the structuring of the space as a place for socialization and coexistence of users, besides serving as support for other activities such as: supporting objects, children’s games, or even as a table. Seats allow the user to enjoy the space to the fullest, giving a view of the events, being a determining factor for the user's choice. This study investigates the user's relationship with seating and its influence on the use of public spaces, focusing on the physical characteristics of seating. Through a simulation experiment, parametric design was used to manipulate variables related to seating, and photomontages were used to create stimuli where the same environment simulates the use of different furniture. The perception, suitability and preference for a given furniture is then investigated through a semantic differential questionnaire applied to users of a public space. It is also worth mentioning that the photomontages were made from an existing park, located in the city of Santa Maria - RS, seeking an approximation of the real condition of the space to subsequently investigate the influence of the seats on the permanence of users in the space in question. This study sought to validate the hypotheses established about the influence of seat design on the user's decision to stay or not in the space, besides exploring how the physical characteristics of the seats are perceived by these users. At the end of the research, it was possible to arrive at results of which seating characteristics can be used as design guidelines for seating designs in public spaces.